Parenting in Improving the Ability of Self-Care in Children with Autism Spectrum Disorder - Sukardi, Sharon Gagat Raina; Ambarwati, Krismi Diah (Faculty of Psychology, Universitas Semarang, 2025)
Autism is not only a deficit in communication and behavior, but it also experiences limitations of self-care. This causes them to require appropriate parenting to develop their ability in self-care in order to create a more independent life. This study aims to explore parenting patterns in improving the ability of self-care in children with ASD using the parenting dimension theory by Baumrind. This study used the qualitative method with a phenomenology approach. Data collection was carried out by interviews and observation. Informants consisted of two families who have children with ASD with an age range of 6-12 years old. This study demonstrated that authoritative parenting is effective parenting because it prioritizes a balance between freedom and guidance. This can form the ability for self-care, especially in children with ASD.